Monitoring electrochemical methanol oxidation and CO coverage using Pt deposited SPR sensor platform. (19th July 2021) - Choi, Baeck B.; Jo, Jae Hyeon; Bice, Jason; Taylor, Curtis; Jiang, Peng; Yoo, Sung Jong
Summary: In order to apply the surface plasmon resonance (SPR) sensing to the study of heterogeneous catalytic reactions, in addition to the metals and dielectrics that the SPR platform already has, a layer or particle that can additionally act as a catalyst is required. The Au layer (50 nm thick) was formed by sputter deposition on the polycarbonate (PC) grating surface of the original DVD‐R structure, and the Pt layer was additionally formed by electrochemical deposition. As‐prepared Au‐covered PC grating exhibits the sensing sensitivity of 973.95 nm/RIU and a figure of merit (FOM) of 69.17. Even after electrochemical Pt deposition, it still showed high sensing sensitivity of 956.57 nm/RIU and FOM of 55.96. In particular, the methanol oxidation and CO coverage on the Pt surface, which are one of the major reactions of the polymer electrolyte membrane fuel cells (PEMFCs), were monitored using Pt deposited SPR sensor. As a result, as the applied potential for methanol oxidation increased and the CO coverage increased, the SPR sensor showed a blue‐shift trend. This is probably due to the process of dehydrogenation of methanol (CH3 OH) molecules to CO and CO2, and the replacing process the water on the Pt surface with CO. Abstract : Development of Pt‐deposited nanostructure‐based SPR sensor platform for in‐situ heterogeneous catalysis study Check the SPR sensing sensitivity (nm/RIU) and FOM (1/S) of Pt‐deposited nanostructure‐based SRP sensor platform using electrochemical deposition, sputter deposition, FDTD simulation, etc. Applied to monitoring the methanol oxidation reaction, CO coverage on Pt surface, one of the major electrode reactions of polymer electrolyte membrane fuel cells (PEMFCs).